Exploring Subjective Employability Outcomes Influenced by Curriculum and Personal Factors in the Cambodian Context - Hornmann Banh (Journal of General Education and Humanities, 2025)
This qualitative study explores how curriculum quality and personal factors shape TESOL students’ and graduates’ perceptions of their employability. The researcher has adopted a constructivist approach to analyse 37 semi-structured interviews with current students and alumni from a four-year TESOL undergraduate program at a private Cambodian university. The findings reveal that curriculum factors, such as content relevance, the balance between teaching theory and practice, and instructional quality, significantly impacted graduates’ confidence and employability. Practical experiences, including teaching practicum and micro-teaching, were crucial in enhancing self-efficacy and job readiness, while many participants found theoretical courses irrelevant to their careers. Personal factors, such as self-efficacy, motivation, social capital, and resilience, further influenced subjective employability outcomes. Graduates with higher self-confidence were more proactive in pursuing jobs, while strong networks led to faster employment. This study contributes to the TESOL employability literature and offers actionable insights for improving curriculum design, student support, and career services. Recommendations include more practical learning opportunities, better mentorship and networking, and fostering a growth mindset to enhance resilience and adaptability in graduates.